2010
DOI: 10.1007/s11356-010-0326-y
|View full text |Cite
|
Sign up to set email alerts
|

Esterase inhibition in tadpoles of Scinax fuscovarius (Anura, Hylidae) as a biomarker for exposure to organophosphate pesticides

Abstract: (1) Tadpoles can be adequate sentinel organisms in biomonitoring studies of OP contamination; (2) AChE was more sensitive than CbE to diazinon; (3) tadpoles from earlier developmental stages seems to be less responsive to OPs; (4) AChE activity was sensitive to diazinon in both development stages, being a better OP biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
1
10
0
3
Order By: Relevance
“…79) The relative activity of these enzymes cannot be simply compared between these tadpoles due to the different fractions of tissue homogenates together with a substrate specificity in CaE, but the BchE activity seems to be lower than the other two. By using the post-mitochondrial supernatant of tissue homogenates from tadpoles of eleven species, Lajmanovich et al 80) have reported large variations in the activity of three esterases.…”
Section: Esterasesmentioning
confidence: 99%
See 1 more Smart Citation
“…79) The relative activity of these enzymes cannot be simply compared between these tadpoles due to the different fractions of tissue homogenates together with a substrate specificity in CaE, but the BchE activity seems to be lower than the other two. By using the post-mitochondrial supernatant of tissue homogenates from tadpoles of eleven species, Lajmanovich et al 80) have reported large variations in the activity of three esterases.…”
Section: Esterasesmentioning
confidence: 99%
“…The presence of CaE isoforms with the optimal pH around 8 was shown in S. fuscovarius not only by no-saturation kinetics in the Lineweaver-Burk plot of the enzyme activity, but also by the presence of at least five esterasic bands in the zymogram after staining with α-and β-naphthyl acetate. 79) Phenyl methyl sulfonyl fluoride (PMSF) generally inhibits most esterases, but tetramonoisopropyl pyrophosphorotetra-mide (iso-OMPA) and 2-(O-cresyl)-4H-1,3,2-benzoxaphorin-2-oxide (CBDP) specifically inhibit BchE and CaE, respectively. 10) PMSF specifically reduced the CaE activity in S. fuscovarius, while iso-OMPA caused no effects on AchE and CaE.…”
Section: Esterasesmentioning
confidence: 99%
“…Para alguns pesticidas dos grupos dos organofosforados e carbamatos sabe-se que seus efeitos tóxicos envolvem mudanças nas atividades de Besterases, como a acetilcolinesterase (AChE), e de glutationa S-transferase (GST), que são neurotransmissores (LEITE et al, 2010;LAJMANOVICH et al, 2010;. Estes pesticidas agem sobre os receptores destas enzimas, podendo inibir as sinapses durante uma transmissão nervosa e impedindo que haja um feedback positivo para execução da função de estímulos nervosos e sensoriais e desintoxicação bioquímica (AMIARD- TRIQUET et al, 2013).…”
Section: Experimento De Exposição Crônicaunclassified
“…Nenhum dos herbicidas manipulados no presente estudo é considerado inibidor de colinesterases (PPDB, 2011 (VIOQUE-FERNADEZ et al, 2007;LEITE et al, 2010;XING et al, 2013). Mas, deve-se lembrar de que neste trabalho houve troca total da solução a cada 7 dias e que portanto os girinos foram expostos constantemente as mesmas concentrações ao longo do experimento não permitindo uma recuperação por diminuição da concentração ou quebra do composto em subprodutos por longo período.…”
Section: Experimento De Exposição Crônicaunclassified
See 1 more Smart Citation